»Lean« und »agil« im Büro - Langes, Barbara (Forschung aus der Hans-Böckler-Stiftung, 2018)
The office work is being completely reorganized in the current digital transformation. Central to this are concepts such as »lean production« and »agile methods«. The book shows the implications of this development for the workforce of employees through case studies from the areas of software development, engineering, metal and electrical industry. A fundamental change in employee work with an uncertain outcome is discernible. Is office work on the digital assembly line or a departure into a new humanization of the world of work? The book provides answers to these questions and shows that the result of development depends on our conscious design.